Genome mining and transcriptional analysis of bacteriocin genes in enterococcus faecium CRL1879 - Suárez, Nadia Elina (2015)
Among 151 bacterial isolates from nine artisanal cheeses, Enterococcus faecium CRL 1879 showed antibacterialactivity against the food-borne pathogen Listeria monocytogenes. The isolate produced a proteinase K-sensitivecompound in the cell free supernatant. Genome analysis demonstrated the presence of enterocin A, enterocin B,enterocin P, enterocin SE-K4-like and enterocin X biosynthetic gene clusters. Nucleotide sequences encoding for aputative two-component bacteriocin were detected using bioinformatics tools, here named enterocin CRL1879αβ.A transcriptional analysis of all bacteriocin genes by quantitative real time PCR analysis (qRT-PCR) revealed thetranscription of each enterocin gene at different levels. Finally, analysis of bacteriocin genes distribution in 251 E.faecium bioprojects was performed and compared to those identify in E. faecium CRL1879. The discriminative analysisdemonstrated that bacteriocin genes are widely distributed among Enterococcus, independently of the origin of thestrain.The results presented in this paper represent a unique finding since this is the first demonstration of an E. faeciumstrain isolated from an artisanal cheese with the complete genetic machinery to produce six classes II and one class III bacteriocins.